Canciones para los hatos y los cultivos: (y algunas reflexiones sobre la experiencia religiosa) - Salomon, Frank (2025)
Rapaz, a community in the upper Checras (province of Oyón), has a temple in the hills that organizes Andean practice and ritual. It uses Quechua I from the Yaru variety, with current endangered language status. This ethnography focuses on songs that sacralize agriculture and another ritual dialogue dedicated to the promotion of cattle. Next, it considers the relevance of phenomenological methodology for developing an anthropology of religion that is not (overly) reductionist.